Takeover - Black, Lisa, 1963- (Black, Lisa, 1963- Theresa MacLean novels., 2008)
What initially appears to be a bank heist turns into something far more complex and deadly. When forensic scientist Theresa MacLean seizes the opportunity to trade places with the city's best hostage negotiator, she must decide what she is willing to sacrifice in order to save the lives of innocent people as well as her own.